Multilayer body including a metal layer for diffuse transillumination - Patent Application 20070229633

By using the thermoplastic polymer support layer of aromatic polycarbonate and rubber-modified vinyl (co) polyester in automotive interior and exterior applications, and combining multi-layer metal electroplating technology to form a multi-layer metal structure, the problem of light transmission and poor light scattering is solved, and the weather resistance of the light source is achieved by achieving uniform lighting and metal plastic combination.

JP2025509105APending Publication Date: 2025-04-11COVESTRO DEUTSCHLAND AG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024549753
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-16
Filing Date
2023-03-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient light transmission and light scattering in automotive interior and exterior applications, resulting in uneven lighting of the light source, and there are problems such as poor bonding between metal and plastic and insufficient light transmission in the process of metal plastic electroplating.

Method used

A thermoplastic polymer containing aromatic polycarbonate and rubber modified vinyl (co) polyester is used as a support layer, and a multi-layer metal structure is formed on the support layer through multi-layer metal plating technology, including metal layers such as copper, nickel and titanium nitride, and a light-transmissive mittance area is formed by partially removing the metal layer.

Benefits of technology

High-light transmissive mittance and high-light scattering effects are achieved, ensuring uniform lighting of the light source in multi-layer articles, and improving the bonding strength and weather resistance of metal and plastic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509105000001
    Figure 2025509105000001
  • Figure 2025509105000002
    Figure 2025509105000002
  • Figure 2025509105000003
    Figure 2025509105000003
Patent Text Reader

Abstract

The present invention relates to a multi-layer body comprising (I) a support layer made of a special thermoplastic polycarbonate molding compound and (II) a metal layer having one or more recesses. The present invention also relates to a lighting or display unit comprising the multi-layer body and a light source, to a method for producing the multi-layer body, and to the use of the special thermoplastic polycarbonate molding compound as a support layer of such a multi-layer body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-layer article comprising a support layer composed of a thermoplastic polycarbonate molding compound and a metal layer, to a lighting or display unit comprising the multi-layer article and a light source, to a method for producing the multi-layer article, and to the use of a thermoplastic polycarbonate molding compound as a support layer in such a multi-layer article. [Background technology]

[0002] Decorative ambient lighting elements or backlit functional / display elements are increasingly used in automotive interior and body applications. The market trend is to switch on / fade in the lighting or functional display only when needed, e.g. to make such elements look different during the day and at night, or to use such ambient dynamic lighting to enhance the perception of space in automotive interiors or to enable the display of situation-appropriate information based on demand.

[0003] These lighting elements or functional elements are, for example, (partially) transilluminatable decorative strips, decorative panels, trim panels, steering wheel covers, consoles, steering wheels and instrument panel carriers, or control elements which may be used to operate various functions of the vehicle, such as start / stop buttons and control elements for the lighting or environmental control of the vehicle, or display elements which may be used to display information as required.

[0004] Such components or components are commonly manufactured from engineered thermoplastics because they allow high individuality and functional integration of parts in molding processes, particularly injection molding, that are simple and cost-effective to implement on an industrially large scale.

[0005] It is often desirable to provide the visible surfaces of such components or components made from technical thermoplastics with decorative layers in order to adapt their appearance, haptics and / or resistance to environmental influences, e.g. light-, UV- or heat-, chemical- or scratch-resistance of the surface appearance to the technical requirement profile of such components or to customer demands for a high-quality and differentiated component appearance. Metal surfaces are in great demand in this context. These can in principle be applied to the thermoplastic body by various methods, e.g. metal vapor deposition, film insert molding of metal foils or electroplating. Electroplating in particular has been proven in industry as a method for applying metal layers to plastic substrates when the aim is to produce components with good adhesion between the metal layer and the plastic main substrate and with mechanical wear or corrosion resistance, for example for automotive interior and exterior applications.

[0006] To achieve transilluminability, the metal layer is cut, i.e. in certain areas of the component or element, the metal layer is not applied from the start or said layer is removed again in a subsequent step down to the plastic main support. These cuts are also called cutouts or breakthroughs in the following. These cutouts can be, for example, in the form of symbols, patterns, holes, lines or letters. It is also possible for them to be point-like cutouts arranged in the form of symbols, patterns, holes, lines or letters.

[0007] However, to achieve a transilluminatable component or component, the plastic main support also needs to be transilluminatable, i.e. exhibit good light transmission, at the typical thickness of the respective component. Typically, it is intended that the support layer can be transilluminated using a visible light source (i.e. light in the wavelength range of 380 nm to 780 nm).

[0008] For an attractive visual impression, it is often also desired that the plastic main support at least to some extent scatters the light from a point source, e.g. an LED, thus achieving a diffuse lighting appearance of the transilluminated component. Otherwise, the light source would be visible to the observer and / or the desired visual effect when the light source is turned on would be limited to only a small area of ​​the multilayer article. To achieve such a diffuse light impression of the surface of a multilayer article transilluminated by a point source, it is necessary that the support layer has, on the one hand, the highest possible transmittance of the visible light incident thereon, and, on the other hand, a light diffusivity, i.e., a half-value angle as high as possible, which is accompanied by a highest possible scattering of the light cone caused by the passage of the support layer by the point source. The higher this half-value angle, the more spatially uniform the perceived illuminance of the light emitted by the point source after passing through the support layer. Also, the higher the half-value angle of the support layer, the larger an area can be transilluminated by the point source with a spatially approximately uniform light intensity. The transmittance and light diffusivity (half-value angle) of a material generally cannot be adjusted independently and generally go in opposite directions to each other. Modifying a material, for example optimizing its light diffusion by changing its composition, generally leads to a decrease in the transmission, in particular also both variables depend on the layer thickness of the transilluminated material, where as the layer thickness increases the transmission of the semi-transparent material decreases and the light diffusion increases.

[0009] Transilluminatable multi-layer articles including a metal layer are known. Patent document 1 discloses a component decorated by electroplating with a symbol or structure transilluminatably introduced on its surface, where the component is manufactured by injection molding from an electroplatable plastic, and the symbol is applied from a non-electroplatable electrostable coating system or the symbol is printed on the component. Once the electroplating process is complete, the component can be transilluminated from its uncoated, metal-free backside with a suitable light source, making the symbol visible.

[0010] A similar approach is described in US Pat. No. 5,399,633, which discloses a method for producing, in particular, electroplated plastic components with tactile and optical interstitial structures, in which an island structure of an electrostable coating is applied onto an electroplatable plastic component, and subsequent electroplating of the component is carried out in the uncoated areas, so that only the islands of the peripheral structure remain uncoated, and the structures around the islands are coated.

[0011] US Pat. No. 5,399,433 discloses a method for producing an electroplated element with a backlightable symbol, in which the initially formed first metal layer is partially removed to expose the symbol, and then in a final step the electroplating on the first metal layer is finished and the revealed symbol is cut out of the electroplating. US Pat. No. 5,399,433 discloses that particularly good results are achieved when the body is made of ABS (acrylonitrile-butadiene-styrene) or ABS / PC (acrylonitrile-butadiene-styrene / polycarbonate). Removal of the first metal layer can be performed by etching, especially when copper is used. When nickel, which has a relatively small layer thickness, is used, removal can also be performed by laser ablation.

[0012] US Patent No. 5,399,633 discloses a metallized plastic component having a transilluminable structure with a day and night design and a method for manufacturing the plastic component. The metallized plastic component comprises a body made of at least one translucent plastic, on which a metal layer is applied, said metal layer having at least one transilluminable structure introduced in the form of a dot matrix. It is disclosed that the plastic blank is preferably at least partially composed of polyamide, ABS or an ABS / polycarbonate blend.

[0013] Patent Document 5 discloses a method for producing a transilluminatable electroplated thermoplastic part and a transilluminatable thermoplastic part having an electroplated surface, comprising the following process steps: coating a thermoplastic part made of a transparent amorphous plastic with an opaque layer of electroplateable plastic, removing the electroplateable plastic by an ablative laser beam in the region of the symbol, and applying an electroplating layer to the electroplateable plastic. It is disclosed that particularly effective electroplating is achieved when using acrylonitrile-butadiene-styrene copolymer (ABS) as the electroplateable plastic.

[0014] Such components or components used in automotive interior and exterior applications require further performances such as good thermoplastic processability (melt flowability), high material ductility, especially even at low temperatures, and high heat distortion resistance. Thermoplastics suitable for such applications and therefore established in such applications, such as polycarbonate, acrylonitrile-butadiene-styrene terpolymer (ABS) and blends of these two thermoplastics, either show poor electroplating behavior, as in the case of transparent polycarbonate or polycarbonate compounds with scattering additives, or in some cases also have too low light diffusion and / or achieve only insufficient metal-plastic bonding in established electroplating processes, or show good electroplating behavior but insufficient light transmission, as in the case of ABS plastics and ABS / PC or PC / ABS blends used in this application field so far.

[0015] It is therefore desirable to provide a multi-layer article capable of diffuse transillumination with improved light yield, comprising a body made of a thermoplastic processable material and a decorative metal layer with cutouts, where the thermoplastic processable material meets the typical performance requirements demanded by the automotive industry for materials for manufacturing components used in interior and exterior applications. It was further desirable to provide a method for manufacturing such a multi-layer article, where the decorative metal layer is applied to the body of thermoplastic processable material by an electrochemical deposition process industrially established in plastic electroplating, achieving a stable bond.

[0016] For this purpose, the support material had to exhibit, on the one hand, an improved light transmittance in the visible wavelength range and high light diffusion, i.e. a combination of a high half-value angle and good properties in the industrially established plastic electroplating processes, and, on the other hand, good thermoplastic processability (melt flowability), high material ductility, especially even at low temperatures, and high thermal distortion resistance. [Prior art documents] [Patent documents]

[0017] [Patent Document 1] German Utility Model No. 202013009793 [Patent Document 2] German Patent Application Publication No. 102010053165 [Patent Document 3] DE 10208674 [Patent Document 4] International Publication No. 2017063768 [Patent Document 5] DE 10320237 Summary of the Invention

[0018] Surprisingly, the above objectives are (I) a support layer composed of a thermoplastic molding compound containing the following A), B), and C); (II) a metal layer, preferably a multi-ply metal layer, containing at least one cutout; A multi-layer article comprising: A) at least one representative selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) a rubber-modified vinyl (co)polymer consisting of the following B.1) and B.2): C) optionally at least one further component selected from polymer additives and blending partner polymers, B.1) 80% to 95% by weight of structural units derived from at least one vinyl monomer, based on the rubber-modified vinyl (co)polymer B; and B.2) 5% to 20% by weight, based on the rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature below -50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene; Here, the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below; (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and trapped in rubber particles; Including, (i.1) rubber particles grafted with a vinyl (co)polymer composed of structural units of B.1, and (i.2) vinyl (co)polymers also composed of structural units of B.1 entrapped in rubber particles as a separate dispersed phase, wherein the dispersed phase of (i) has a median diameter D50 of 0.7 μm to 2.0 μm as measured by ultracentrifugation; The thermoplastic molding compound contains less than 2% by weight of a rubber-based graft polymer different from component B), and The thermoplastic molding compound has a rubber content of at least 2.0% by weight; It has been found that this is achieved by a multi-layer article in which the at least one cut-out is in the form of at least one symbol, a pattern, a hole, a line or a letter, or in the form of dot-like cut-outs arranged in the form of at least one symbol, a pattern, a hole, a line or a letter.

[0019] In the context of the present application, the support layer (I) is also referred to synonymously as plastic support or plastic support layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] In a preferred embodiment, the thermoplastic molding compound of the support layer (I) is 30% to 85% by weight, more preferably 50% to 82% by weight, even more preferably 58% to 82% by weight, and most preferably 65% ​​to 75% by weight of component A; 14% to 69% by weight, more preferably 17% to 49% by weight, even more preferably 17% to 41% by weight, and most preferably 24% to 34% by weight of component B; 0.05% to 20% by weight, more preferably 0.1% to 10% by weight, even more preferably 0.2% to 5% by weight, and most preferably 0.3% to 2% by weight of component C; Includes.

[0021] In a preferred embodiment, the molding compound of the support layer (I) comprises less than 1% by weight, more preferably less than 0.5% by weight, even more preferably less than 0.2% by weight of a rubber-based graft polymer different from component B).The molding compound most preferably does not comprise a rubber-based graft polymer different from component B).

[0022] In a preferred embodiment, the molding compound of the support layer (I) has a rubber content in the range of 2.0% to 6% by weight, more preferably in the range of 2.5% to 5% by weight, even more preferably in the range of 2.6% to 4.1% by weight, and most preferably in the range of 2.7% to 3.3% by weight.

[0023] The above preferred ranges of components A and B and C can be combined with each other as desired.

[0024] In a preferred embodiment, the support layer (I) consists to the extent of at least 80% by weight, more preferably at least 95% by weight, even more preferably at least 99% by weight, and most preferably 100% by weight, of a thermoplastic molding compound consisting of components A, B, and C.

[0025] The multilayer article is suitable for transillumination with visible light using a light source, i.e. the multilayer article is preferably transilluminable. The light source is arranged such that light first enters the support layer (I) and exits through the cutout in the metal layer (II). The light source is preferably an LED light source.

[0026] Transilluminatable is to be understood to mean that switching on the light source changes the visual impression of the side opposite the light source, i.e. the visible side of the component or element in the installed state.

[0027] In a preferred embodiment, the multilayer article has, at least in a partial region of its actual local thickness, i.e. in the cut-out, a transmittance at least at one wavelength in the wavelength range of the spectrum from 380 nm to 780 nm of at least 10%, more preferably at least 25%, even more preferably at least 40%, most preferably at least 45%, where the transmittance is taken from a transmission spectrum measured according to the standard in DIN / ISO 13468-2 (2006 edition).

[0028] The present invention further provides the use of a molding compound consisting of components A, B and C as described above, and further specified features, as a support layer (I) in the above multi-layer article.

[0029] The invention further provides an illumination or display unit comprising a multilayer article as defined above and a light source emitting light having at least one wavelength in the wavelength range of the spectrum from 380 nm to 780 nm, the light source being positioned such that the support layer is transilluminated by the light emitted by the light source.

[0030] The present invention further provides a method for making a transilluminatable multi-layer article, comprising the steps of: (1) forming a plastic substrate from the thermoplastic molding compound described above; (2) optionally covering at least a portion of the surface of the plastic support opposite the visible side of the multilayer article, and optionally a portion of the visible surface of the plastic support, with an electrostable layer, preferably a coating, which locally prevents chemical, electrochemical or physical metal deposition in process step (3a) and thereby locally prevents electroplating in this area of ​​the plastic support in process step (3c); (3) electrochemically depositing a metal layer, preferably multiple plies, onto the portions of the surface of the plastic support not covered with the electrostable layer in step (2); In addition, process step (3) includes the following sub-steps: (3a) producing a thin film metal layer, preferably a layer of palladium, copper or nickel, on a plastic support, preferably in a chemical, electrochemical or physical process selected from deposition from a colloidal solution, direct metallization or vapor deposition; (3b) optionally partially removing the thin metal layer produced in process step (3a) by a process preferably selected from etching or laser ablation to produce areas on the plastic support that are not covered with the thin metal film; (3c) electroplating a preferably multi-ply metal surface coating comprising at least one electrochemical metal deposition step; It should be noted that areas on the plastic support that are not covered with the thin metal film produced in process step (3b) are not electroplated; (4) optionally, by mechanical, chemical and / or physical processes, locally removing the preferably multi-ply metal layer applied to the surface of the plastic support, forming breakthroughs in the metal layer and locally exposing the surface of the plastic support; wherein at least one of optional process steps (2), (3b) and (4) is used in a process, preferably with the result that at least one cutout in the multi-ply metal layer occurs on the visible side of the multilayer article, and if in process step (3) a metal layer is also provided on the side opposite the visible side of the multilayer article, at least one cutout in the metal layer also occurs on the side opposite the visible side of the multilayer article.

[0031] If in process step (3) a metal layer is electrochemically provided on both the visible side and on the side opposite to the visible side of the multilayer article, the at least one cutout introduced on both sides of the multilayer article by at least one of the optional process steps (2), (3b) and (4) is preferably realized in directly opposing areas of the support layer (I).

[0032] The "visible side" of a multilayer article should be understood to mean the side that is visible in the final application of the multilayer article, i.e. in its installed context, for its intended function. If the multilayer article is a component of a lighting or display unit through which the multilayer article is transilluminated by a light source, the visible side is the side of the multilayer article opposite the light source in the lighting or display unit.

[0033] It is preferred to have a metal layer only on the visible side of the multi-layer article.

[0034] A preferred embodiment of the process is described below.

[0035] Composition of the support layer Ingredient A The aromatic polycarbonates and / or aromatic polyestercarbonates of component A suitable according to the invention are known from the literature or can be prepared by methods known from the literature (for the preparation of aromatic polycarbonates, see, for example, Schnell, "Chemistry and Physics of Polycarbonates", Interscience Publishers, 1964, and also DE-A-1 495 626, DE-A-2 232 877, DE-A-2 703 376, DE-A-2 714 544, DE-A-3 000 610, DE-A-3 832 396; for the preparation of aromatic polyestercarbonates, see, for example, DE-A-3 007 934).

[0036] Aromatic polycarbonates are prepared, for example, by reacting diphenols with carbonyl halides, preferably phosgene and / or aromatic dicarbonyl dihalides, preferably dihalides of benzenedicarboxylic acids, by interfacial methods, optionally using chain terminators, such as monophenols, and optionally using trifunctional or higher branching agents, such as triphenols or tetraphenols. Preparation via melt polymerization methods by reacting diphenols with, for example, diphenyl carbonate is also possible.

[0037] The diphenols for the preparation of the aromatic polycarbonates and / or aromatic polyester carbonates preferably have the formula (I): [ka] (In the formula, A is a single bond, C 1 ~C 5 Alkylene, C 2 ~C 5 Alkylidene, C 5 ~C 6 Cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO 2 -, optionally fused with further aromatic rings containing heteroatoms, C 6 ~C12 Arylene, or a compound represented by formula (II) or (III): [ka] Based on B, in each case, C 1 ~C 12 - alkyl, preferably methyl, halogen, preferably chlorine and / or bromine, x is, independently in each occurrence, 0, 1, or 2; p is 1 or 0, and R 5 and R 6 For each X 1 can be selected individually, each independently being hydrogen or C 1 ~C 6 alkyl, preferably hydrogen, methyl or ethyl; X 1 is carbon, and m is an integer from 4 to 7, preferably 4 or 5, provided that at least one atom X 1 R on top 5 and R 6 is a diphenol of the formula (wherein both are alkyl).

[0038] Preferred diphenols are hydroquinone, resorcinol, dihydroxydiphenols, bis(hydroxyphenyl)-C 1 ~C 5 Alkane, bis(hydroxyphenyl)-C 5 ~C 6 Cycloalkanes, bis(hydroxyphenyl) ethers, bis(hydroxyphenyl) sulfoxides, bis(hydroxyphenyl) ketones, bis(hydroxyphenyl) sulfones, and α,α-bis(hydroxyphenyl) diisopropylbenzene, and their ring brominated and / or ring chlorinated derivatives.

[0039] Particularly preferred diphenols are 4,4'-dihydroxybiphenyl, bisphenol A, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, and their dibrominated and tetrabrominated or dichlorinated and tetrachlorinated derivatives, such as 2,2-bis(3-chloro-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, or 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane. 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) is particularly preferred.

[0040] The diphenols can be used individually or in the form of any desired mixtures. The diphenols are known from the literature or can be obtained by literature methods.

[0041] Examples of chain terminators suitable for the preparation of thermoplastic aromatic polycarbonates include phenol, p-chlorophenol, p-tert-butylphenol or 2,4,6-tribromophenol, as well as long-chain alkylphenols, such as 4-[2-(2,4,4-trimethylpentyl)]phenol, 4-(1,3-tetramethylbutyl)phenol according to DE-A-2842005, and mono- or dialkylphenols having a total of 8 to 20 carbon atoms in the alkyl substituent, such as 3,5-di-tert-butylphenol, p-isooctylphenol, p-tert-octylphenol, p-dodecylphenol, as well as 2-(3,5-dimethylheptyl)phenol and 4-(3,5-dimethylheptyl)phenol. The amount of chain terminator used is generally between 0.5 mol% and 10 mol% relative to the total moles of the diphenols used in each case.

[0042] The thermoplastic aromatic polycarbonates preferably have an average molecular weight (weight-average M) of 20 000 g / mol to 40 000 g / mol, more preferably 24 000 g / mol to 32 000 g / mol, particularly preferably 26 000 g / mol to 30 000 g / mol, measured by GPC (gel permeation chromatography) calibrated against bisphenol A polycarbonate standards with dichloromethane as eluent, calibration with linear polycarbonates of known molar mass distribution (prepared from bisphenol A and phosgene) from PSS Polymer Standards Service GmbH (Germany) and calibration according to method 2301-0257502-09D (German version of 2009) from Currenta GmbH & Co. OHG (Leverkusen). w ). The eluent is dichloromethane. Column: combination of cross-linked styrene-divinylbenzene resin. Analytical column diameter: 7.5 mm; length: 300 mm. Column material particle size: 3 μm-20 μm. Solution concentration: 0.2 wt.%. Flow rate: 1.0 ml / min, solution temperature: 30°C. UV and / or RI detection is used.

[0043] The preferred ranges provide a particularly advantageous balance of mechanical and rheological properties in the compositions of the present invention.

[0044] The thermoplastic aromatic polycarbonates can be branched in a known manner, preferably by incorporating 0.05 mol % to 2.0 mol % of trifunctional or more than trifunctional compounds, for example compounds with three or more phenolic groups, relative to the total sum of the diphenols used. It is preferred to use linear polycarbonates, more preferably linear polycarbonates based on bisphenol A.

[0045] Both homopolycarbonates and copolycarbonates are suitable. The copolymers of the invention according to component A can also be prepared using polydiorganosiloxanes having 1% to 25% by weight, preferably 2.5% to 25% by weight, of hydroxyaryloxy end groups, based on the total amount of diphenols used. These are known (US Pat. No. 3,419,634) and can be prepared by methods known from the literature. Likewise suitable are polydiorganosiloxane-containing copolycarbonates, the preparation of which is described, for example, in DE-A-3334782.

[0046] The aromatic dicarbonyl dihalides for the preparation of aromatic polyester carbonates are preferably the diacyl dichlorides of isophthalic acid, terephthalic acid, diphenyl ether 4,4'-dicarboxylic acid, and naphthalene-2,6-dicarboxylic acid.

[0047] Mixtures of the diacyl dichlorides of isophthalic and terephthalic acid in ratios between 1:20 and 20:1 are particularly preferred.

[0048] In the preparation of polyester carbonates, carbonyl halides, preferably phosgene, are additionally used as difunctional acid derivatives.

[0049] In addition to the above-mentioned monophenols, the chain terminators useful for the production of aromatic polyester carbonates include the chlorocarbonates and acid chlorides of aromatic monocarboxylic acids (C 1 ~C 22 alkyl or halogen atoms), and aliphatic C 2 ~C 22 Monocarboxylic acid chlorides are included.

[0050] The amount of chain terminator in each case is between 0.1 mol % and 10 mol % based on the number of moles of diphenol in the case of phenolic chain terminators and based on the number of moles of dicarboxylic acid dichloride in the case of monocarboxylic acid chloride chain terminators.

[0051] In preparing the aromatic polyester carbonates, it is also possible to use one or more aromatic hydroxycarboxylic acids.

[0052] The aromatic polyestercarbonates may be linear or branched in a known manner (see DE-A-2 940 024 and DE-A-3 007 934), whereby linear polyestercarbonates are preferred.

[0053] The branching agents used are, for example, trifunctional or polyfunctional carboxylic acid chlorides, such as trimesyl trichloride, cyanuric acid trichloride, 3,3',4,4'-benzophenonetetracarboxylic acid tetrachloride, 1,4,5,8-naphthalenetetracarboxylic acid tetrachloride or pyromellitic acid tetrachloride, in an amount of 0.01 mol % to 1.0 mol % (relative to the dicarboxylic acid dichloride used), or trifunctional or polyfunctional phenols, such as phloroglucinol, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)hept-2-ene ... The branching agents are 2,2-bis[4,4-bis(4-hydroxyphenyl)cyclohexyl]propane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, tetra(4-hydroxyphenyl)methane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-[4-hydroxyphenylisopropyl]phenoxy)methane, and 1,4-bis[4,4'-dihydroxytriphenyl)methyl]benzene. Phenol-based branching agents can be initially charged with diphenols, and acid chloride branching agents can be introduced with acid dichlorides.

[0054] The proportion of carbonate structural units in thermoplastic aromatic polyester carbonates can be varied as desired.The proportion of carbonate groups is preferably at most 100 mol%, particularly preferably at most 80 mol%, particularly preferably at most 50 mol%, based on the sum of ester groups and carbonate groups.Both the ester and carbonate moieties of aromatic polyester carbonates can be present in the polycondensate in the form of blocks or in random distribution.

[0055] The thermoplastic aromatic polycarbonates and polyester carbonates may be used alone or in any desired mixtures.

[0056] As component A it is preferred to use linear polycarbonates based exclusively on bisphenol A.

[0057] Component B Component B is a rubber-modified vinyl (co)polymer composed of the following B.1) and B.2): B.1) 80% to 95% by weight, preferably 83% to 93% by weight, more preferably 85% to 92% by weight, of structural units derived from at least one vinyl monomer, based on the rubber-modified vinyl (co)polymer B; and B.2) Rubber-modified vinyl (co)polymers B containing 5% to 20% by weight, preferably 7% to 17% by weight, more preferably 8% to 15% by weight, based on B.2, of structural units derived from 1,3-butadiene, preferably at least 50% by weight, preferably at least 70% by weight, particularly preferably 100% by weight, based on B.2, of structural units derived from 1,3-butadiene, and having a glass transition temperature T g one or more elastomeric graft substrates having Here, the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below; (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and not trapped in rubber particles; Including, (i.1) rubber particles grafted with a vinyl (co)polymer composed of structural units of B.1, and (i.2) vinyl (co)polymers also composed of structural units of B.1 entrapped in rubber particles as a separate dispersed phase, And the dispersed phase of (i) has a median diameter D50, measured by ultracentrifugation, of 0.7 μm to 2.0 μm, preferably 0.7 μm to 1.5 μm, in particular 0.7 μm to 1.2 μm.

[0058] Unless otherwise expressly specified in the present invention, the glass transition temperature T g For all components, the T g is determined using the tangent method.

[0059] The rubber modified vinyl (co)polymers of component B preferably have a melt volume flow rate (MVR) of 2 ml / 10 min to 20 ml / 10 min, particularly preferably 3 ml / 10 min to 15 ml / 10 min, in particular 4 ml / 10 min to 8 ml / 10 min, measured at 220° C. and 10 kg piston load according to ISO 1133 (2012 edition). When a mixture of two or more rubber modified vinyl (co)polymers is used as component B, the preferred MVR range corresponds to the average of the MVRs of the individual components weighted by the mass fraction of the components in the mixture.

[0060] Such rubber-modified vinyl (co)polymers B are, for example, B.1 80% to 95% by weight, preferably 83% to 93% by weight, particularly preferably 85% to 92% by weight, of at least one vinyl monomer, based on the rubber-modified vinyl (co)polymer B, B.2 5% to 20% by weight, preferably 7% to 17% by weight, particularly preferably 8% to 15% by weight, based on the rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature of less than -50°C, preferably less than -60°C, particularly preferably less than -70°C, which contain structural units derived from 1,3-butadiene, based on B.2, at least 50% by weight, preferably at least 70% by weight, particularly preferably 100% by weight, The copolymer is prepared by free radical polymerization in the presence of, preferably in a bulk polymerization process.

[0061] The bulk polymerization process preferably used to prepare the rubber modified vinyl (co)polymer B comprises both the polymerization of vinyl monomers B.1 and the grafting of the vinyl (co)polymer thus formed onto the elastomeric graft substrate B.2. Furthermore, in this reaction mode, self-organization (phase separation) leads to the formation of a dispersed phase (i) consisting of (i.1) and (i.2): (i.1) rubber particles grafted with a vinyl (co)polymer composed of structural units of B.1, and (i.2) vinyl (co)polymers also composed of structural units of B.1 entrapped in rubber particles as a separate dispersed phase, Here, the rubber-containing phase (i) is in the form of a dispersion in a rubber-free vinyl (co)polymer matrix (ii) consisting of structural units of B.1 that are not bonded to and are not trapped in the rubber particles.

[0062] In contrast to the other vinyl (co)polymer proportions in component B, the rubber-free vinyl (co)polymer (ii) can be dissolved using a suitable solvent, such as, for example, acetone.

[0063] The size of the dispersed phase (i) in the rubber modified vinyl (co)polymer B thus produced is adjusted via the conditions of the reaction regime, such as, for example, the temperature and the viscosity of the polymer obtained therefrom, as well as the shear from stirring.

[0064] The median particle size D50 is the diameter above which 50% by weight of the particles lie and below which 50% by weight lie. Unless otherwise expressly stated in the present invention, this is determined for all components by ultracentrifuge measurements (W. Scholtan, H. Lange, Kolloid, Z. und Z. Polymere 250 (1972), 782-796).

[0065] The monomers B.1 are preferably B.1.1 60 to 85 parts by weight, particularly preferably 65 to 80 parts by weight, more preferably 70 to 78 parts by weight of styrene, in each case relative to the sum of B.1.1 and B.1.2, B.1.2. 15 to 40 parts by weight, particularly preferably 20 to 35 parts by weight, more preferably 22 to 30 parts by weight, of acrylonitrile, in each case relative to the sum of B.1.1 and B.1.2, and optionally B.1.3 0 to 10 parts by weight, preferably 0 to 7 parts by weight, more preferably 0 to 5 parts by weight, of methyl methacrylate or n-butyl acrylate, in each case relative to 100 parts by weight of the total of B.1.1 and B.1.2, It is a mixture consisting of:

[0066] In a further preferred embodiment, monomer B.1 is a mixture of 22 to 26 parts by weight of acrylonitrile and 74 to 78 parts by weight of styrene, optionally containing up to 10 parts by weight, particularly preferably up to 5 parts by weight, of n-butyl acrylate or methyl methacrylate, where the sum of the parts by weight of styrene and acrylonitrile is 100 parts by weight.

[0067] It is especially preferred if B.1 does not include B.1.3, and the above mentioned preferred ranges apply to B.1.1 and B.1.2.

[0068] Preferred graft substrates B.2 are butadiene-containing diene rubbers or mixtures of butadiene-containing diene rubbers or copolymers of butadiene-containing diene rubbers or mixtures thereof with further copolymerizable monomers (for example B.1.1 and B.1.2).

[0069] A particularly preferred graft substrate B.2 is a pure polybutadiene rubber. In a further preferred embodiment, B.2 is a styrene-butadiene block copolymer rubber.

[0070] Component B preferably has a polybutadiene content of from 5% to 18% by weight, more preferably from 7% to 15% by weight, especially from 8% to 13% by weight.

[0071] Particularly preferred rubber-modified vinyl (co)polymers of component B are the bulk-polymerized ABS polymers, as described, for example, in DE-A-2 035 390 (=U.S. Pat. No. 3,644,574) or DE-A-2 248 242 (=GB Pat. No. 1,409,275) or in Ullmanns Enzyklopaedie der Technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry]), Vol. 19 (1980), p. 280 et seq.

[0072] The vinyl (co)polymer (ii) which is not chemically bonded to the rubber substrate(s) B.2 and is not trapped in rubber particles can be formed as a result of its preparation in the polymerization of the graft polymer B, as described above. Likewise, a portion of this vinyl (co)polymer (ii) which is not chemically bonded to the rubber substrate(s) B.2 and is not trapped in rubber particles can be formed in the rubber-modified vinyl (co)polymer of component B as a result of its preparation in a bulk polymerization process, and another portion can be polymerized separately and added to component B as a constituent of component B. In component B, the proportion of the vinyl (co)polymer (ii), regardless of origin, measured as the acetone-soluble portion, is preferably at least 50% by weight, particularly preferably at least 60% by weight, more preferably at least 70% by weight, relative to component B.

[0073] In the rubber-modified vinyl (co)polymer of component B, the vinyl (co)polymer (ii) has a weight average molecular weight M of 70 kg / mol to 250 kg / mol, preferably 130 kg / mol to 200 kg / mol, in particular 150 kg / mol to 180 kg / mol. w has.

[0074] In the context of the present invention, the weight average molecular weight M of the vinyl (co)polymer (ii) in component B w is determined by gel permeation chromatography (GPC) in tetrahydrofuran against polystyrene standards.

[0075] Component B preferably does not contain alkali metals, alkaline earth metals, ammonium or phosphonium salts of saturated fatty acids having 8 to 22 carbon atoms, resin acids, alkylsulfonic acids and alkylarylsulfonic acids, and fatty alcohol sulfates.

[0076] Component B preferably comprises less than 100 ppm, particularly preferably less than 50 ppm and very particularly preferably less than 20 ppm of alkali metal and alkaline earth metal ions.

[0077] Suitable rubber-modified vinyl (co)polymers as component B are, for example, Magnum® 3404, Magnum® 3504 and Magnum® 3904 from Trinseo SA (Luxembourg).

[0078] Component C One or more representatives selected from the group consisting of polymeric additives and polymeric blend partners may optionally be present as component C.

[0079] The polymer additive / partner polymer is preferably selected from the group consisting of lubricants and release agents, stabilizers, colorants, compatibilizers, further impact modifiers different from component B, further polymer constituents different from components A and B (e.g. functional compounding partners or graft polymers with a core-shell structure prepared in an emulsion polymerization process), and fillers and reinforcing agents.

[0080] In a preferred embodiment, no filler or reinforcing agent is present in component C. Even more preferred is the absence of a colorant. Even more preferred is the absence of a blending partner polymer. Even more preferred is the absence of a polymeric component. In a particularly preferred embodiment, neither a filler or reinforcing agent, nor a colorant or blending partner polymer is present. Most preferred is the absence of a filler or reinforcing agent, nor a colorant or polymeric component.

[0081] In a preferred embodiment, at least one polymeric additive selected from the group consisting of lubricants and mold release agents and stabilizers is used as component C.

[0082] In a preferred embodiment, at least one representative selected from the group consisting of sterically hindered phenols, organic phosphites, and organic or inorganic Bronsted acids is used as stabilizer.

[0083] In a preferred embodiment, at least one representative selected from the group consisting of sterically hindered phenols, organic phosphites, and organic or inorganic Bronsted acids is used as stabilizer.

[0084] In a preferred embodiment, fatty acid esters, particularly preferably fatty acid esters of pentaerythritol or glycerol, are used as lubricants and release agents.

[0085] In a particularly preferred embodiment, the C of pentaerythritol 8 ~C 22 Fatty acid esters, glycerol C 8 ~C 22 At least one polymer additive selected from the group consisting of fatty acid esters, tris(2,4-di-tert-butylphenyl)phosphite, 2,6-di-tert-butyl-4-(octadecaneoxycarbonylethyl)phenol, tetrakis(2,4-di-tert-butylphenyl)-4,4-biphenyl diphosphonite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] is used as component C.

[0086] In a further embodiment, Component C does not include a rubber-modified vinyl (co)polymer prepared by emulsion polymerization.

[0087] Preparation of the molding compound for the support layer From components A, B and C according to the invention a thermoplastic molding compound is produced.

[0088] For example, the thermoplastic molding compounds according to the invention can be produced when the individual components of the composition are mixed in a well-known manner and melt-compounded and melt-extruded in customary equipment, such as, for example, internal mixers, extruders and twin-screw extruders, preferably at temperatures between 200°C and 320°C, particularly preferably between 240°C and 300°C, very particularly preferably between 260°C and 290°C.

[0089] In the context of this application, this process is generally referred to as compounding.

[0090] Thus, the term "moulding compound" should be understood to mean the product obtained when the constituents of the composition are melt compounded and melt extruded.

[0091] The mixing of the individual components of the composition can be carried out in a known manner, either sequentially or simultaneously, at temperatures either about 20° C. (room temperature) or higher, i.e., for example, some components can be introduced through the main intake of an extruder and the remaining components can be introduced through a side extruder at a later time during the compounding process.

[0092] metal layer The metal layer (II) is preferably a multi-ply metal layer that is preferably applied in an electroplating process.

[0093] The metal layer has at least one cutout, which may be in the form of, for example, a symbol, a pattern, a hole, a line or a letter, as well as in the form of a dot-like cutout arranged in the form of at least one symbol, a pattern, a hole, a line or a letter.

[0094] The multi-ply metal layer is preferably comprised of at least three, more preferably at least four, metal plies that are distinguishable by microscopic examination and / or chemical analysis.

[0095] Preferably, the thickness of the multi-ply metal layer is from 5 μm to 200 μm, preferably from 10 μm to 60 μm, particularly preferably from 30 μm to 50 μm.

[0096] In a first embodiment, the multi-ply metal layer preferably comprises three metal plies distinguishable by microscopic examination and chemical analysis, namely, starting from the support layer (I): (i) a first ply of copper; (ii) a second ply of nickel; and (iii) a third ply of a metal having high resistance to environmental influences, e.g., preferably chromium; It consists of:

[0097] In a second preferred embodiment, the multi-ply metal layer preferably comprises four metal plies distinguishable by microscopic examination and chemical analysis, namely, starting from the support layer (I): (i) a first ply of nickel; (ii) a second ply of copper; (iii) a third ply of nickel; and (iv) a fourth ply of a metal having high resistance to environmental influences, for example preferably chromium; It consists of:

[0098] The required thickness of the individual metal plies, and thus the total thickness of the metal layer in the multilayer article according to the invention, is determined by the requirements for mechanical properties, resistance to environmental influences, resistance to thermal distortion and further required properties of the component.

[0099] The copper metal plies preferably have a thickness of 10 μm to 50 μm, particularly preferably 15 μm to 30 μm, very particularly preferably 20 μm to 30 μm.

[0100] In a preferred embodiment, the nickel metal layer starting from the support layer (I) and continuing to the copper layer has a thickness no greater than half that of the copper metal layer below it.

[0101] The top metal ply of a metal having high resistance to environmental influences, preferably chromium, preferably has a thickness of 100 nm to 3 μm, particularly preferably 200 nm to 1.5 μm.

[0102] For components in which the nickel metal layer is directly adjacent to the support layer (I), said nickel metal layer usually preferably has a thickness of from 500 nm to 5 μm, particularly preferably from 1 μm to 2 μm.

[0103] The metal layer may be coated on the side opposite the support layer with a coating composition. The coating is typically intended to provide mechanical protection against abrasion and scratches and / or protection against weathering effects, i.e. precipitation, temperature changes and UV radiation. Certain surface haptics or surface optics may also be realized with the coating.

[0104] Suitable coatings are, for example, heat-curable coating systems based on polysiloxane coatings, which can be either single-layer systems or multi-layer systems (with merely an adhesion-promoting primer layer between the substrate and the polysiloxane topcoat).

[0105] It is also possible to use UV-curable coating systems based, for example, on acrylates, urethane acrylates or acryloyl silanes, optionally containing fillers which improve scratch resistance.

[0106] Manufacturing of multi-layer articles The following describes a preferred method for producing a multi-layer article according to the present invention:

[0107] In a first step (1), a support layer (I) is formed from a thermoplastic composition as described above, preferably an extrusion, blow molding, thermoforming or injection molding process, particularly preferably an injection molding process, is used for molding in the manufacture of this support.

[0108] In a subsequent process step, the support layer (I) is electroplated in an electroplating process established for acrylonitrile-butadiene-styrene (ABS) copolymers and their blends with polycarbonate.

[0109] The process parameters in process step (1) are preferably selected so that the support component used in the electroplating process is as stress-free as possible. For this purpose, if an injection molding process is used for molding, it is advantageous to select the lowest possible injection speed, injection pressure and holding pressure, and the highest possible mold temperature. The specific conditions depend on the mold geometry and the mold sprue. A specific injection pressure of 600 bar or less is advantageous. The specific holding pressure preferably starts from the value of the specific injection pressure and is then preferably gradually reduced.

[0110] The mold temperature is preferably in the range of 80°C to 140°C, and particularly preferably in the range of 100°C to 130°C.

[0111] It has also been found to be particularly advantageous and therefore preferred to use a variothermal injection molding process in which, in process step (1), the injection mold is first heated to a temperature above the glass transition temperature of the polycarbonate component A), preferably to at least 150°C, particularly preferably to at least 160°C, and after the polycarbonate composition has been injected into the mold, this temperature is maintained for a holding pressure time, before the mold is cooled to a temperature below the glass transition temperature of the polycarbonate component A), preferably in the range of 80°C to 140°C, particularly preferably in the range of 100°C to 130°C, thereby solidifying and finally demolding. Such a process makes it possible to realize a further improvement in the actual heat distortion resistance of the electroplated components compared to standard injection molding processes.

[0112] The support layer (I) produced in process step (1) can in principle be a sheet, a profile or a three-dimensional component of any desired shape. The support layer (I) produced in process step (1) can also be a film. Such films suitable as support layer (I) are preferably produced in an extrusion process.

[0113] In the particular case in which the support layer (I) is produced in an extrusion or blow molding process, in particular in the special case in which the support layer (I) is an extruded film or an extruded sheet, which is optionally thermoformed, a thermoplastic molding compound which comprises as component A a branched polycarbonate is preferably used for the production of the support layer (I).

[0114] After production in process step (1), the support layer (I) is preferably subjected to intermediate storage until the post-shrinkage has ceased, which typically requires between 10 and 48 hours. This intermediate storage further reduces any stresses still present in the plastic part.

[0115] A second optional process step (2) involves providing at least a portion of the surface of the plastic support opposite the visible side of the multilayer article, and optionally a portion of the visible surface of the plastic support, with an electrostable layer, preferably a coating, which locally prevents chemical, electrochemical or physical metal deposition in a subsequent process step (3a) and thereby locally prevents electroplating in this area of ​​the plastic support in process step (3c).

[0116] The third process step (3) of electrochemical deposition of a multi-layer metal layer on the parts of the surface of the plastic support that are not covered with the electrostable layer in step (2) (electroplating process) comprises the following sub-steps: (3a) producing a thin film metal layer, preferably a layer of palladium, copper or nickel, on a plastic support, preferably in a chemical, electrochemical or physical process selected from deposition from a colloidal solution, direct metallization or vapor deposition; (3b) optionally partially removing the thin metal layer produced in process step (3a) by a process preferably selected from etching or laser ablation to produce areas on the plastic support that are not covered with the thin metal film; (3c) electroplating the multi-ply metal surface coating, which comprises at least one electrochemical metal deposition step; It should be noted that areas on the plastic support that are not covered with the thin metal film produced in process step (3b) are not electroplated.

[0117] An optional fourth process step (4) involves again partially removing, by mechanical, chemical and / or physical processes, the metal layer applied to the surface of the plastic support to form a breakthrough in the metal layer and locally expose the surface of the plastic support.

[0118] In the method according to the invention for producing the multilayer article according to the invention, at least one of the optional process steps (2), (3b) and (4) is used, which results in at least one cutout in the preferably multi-ply metal layer on the visible side of the multilayer article. If in process step (3) a metal layer is also provided on the side opposite to the visible side of the multilayer article, at least one cutout is also produced on this side opposite to the visible side.

[0119] If in process step (3) a metal layer is electrochemically provided on both the visible side and on the side opposite to the visible side of the multilayer article, the at least one cutout introduced on both sides of the multilayer article by at least one of the optional process steps (2), (3b) and (4) is preferably realized in directly opposing areas of the plastic support I.

[0120] It is preferred to have a metal layer only on the visible side of the multi-layer article.

[0121] Preferred is a process in which process step 3a) comprises the following sub-steps: (3a-1) pickling the plastic support produced in process step (1), for example, preferably with chromosulfuric acid, in which in a preferred embodiment a wetting aid (e.g. Entone's Udique™ wetting agent BL2030) is used as a process aid to reduce the surface tension between the plastic support and the pickling agent, followed by chemical reduction of the chromosulfuric acid using a reducing agent, for example iron(II) chloride, followed by thorough rinsing with water to effectively remove chromium residues; (3a-2) activating the thus pretreated plastic support by adsorption of a palladium colloid, preferably a palladium colloid having a tin chloride sheath, onto the support surface; and (3a-3) Breaking the sheath of adsorbed palladium colloids by treatment with dilute Bronsted acid to produce palladium seeds for subsequent deposition of chemical nickel or copper on the plastic support surface.

[0122] Also preferred is a process, in which process step 3c) comprises the following sub-steps: (3c-1) Deposition of chemical nickel or copper from nickel(II) or copper(II) salt solutions using chemical reducing agents, such as dihydrogen phosphite; (3c-2) electrochemical application of a copper metal layer; (3c-3) electrochemical application of a nickel metal layer, and (3c-4) Electrochemical application of a further metal layer having high resistance to environmental influences, for example a preferably chromium metal layer.

[0123] In a further preferred embodiment of the electroplating process, before process step (3a-2), the plastic support from process step (3a-1) is treated with so-called "conditioners" which, as processing aids, improve the adsorption of the palladium colloid in process step (3a-2). These are preferably substances selected from the group of amines, preferably cyclohexanediamines. The "conditioners" are preferably used as aqueous solutions. An additional treatment of the plastic support with an aqueous solution of a Brönsted acid, preferably hydrochloric acid solution, may optionally be carried out before or after the treatment with the "conditioner".

[0124] The degree of palladium adsorption depends in particular on the nature of the palladium colloid and on the conditions in the activation step (3a-2), in particular the activation time, temperature and the concentration of the palladium colloid used.

[0125] The conditions in the activation step (3a-2) and any upstream conditioning steps as described above are preferably such that, after process step (3a-3), a coverage of the plastic substrate surface of 1 m 2 At least 4 mg of palladium per m 2 The coverage of palladium deposited after process step (3a-3) is preferably selected to be at least 5 mg of palladium per m 2 Not more than 50 mg of palladium per m 2 Not more than 30 mg of palladium per unit.

[0126] In process step (3c-1) a closed layer of chemical nickel or copper is applied, preferably having a thickness of 500 nm to 5 μm, particularly preferably 1 μm to 2 μm.

[0127] In a preferred embodiment of the electroplating process, process step (3c-2) comprises a first step (3c-2-1) of electrochemical application of an initial thin reinforcing layer of nickel or copper and a second step (3c-2-2) of electrochemical application of a thicker high-gloss layer of copper metal, in which a higher current density is used in process step (3c-2-2) than in process step (3c-2-1). In a particularly preferred embodiment, the current density in process step (3c-2-2) is at least 30%, particularly preferably at least 50%, higher than the current density in process step (3c-2-1). This preferred embodiment makes it possible to reduce the time required for application of the high-gloss copper metal layer.

[0128] By selecting the process parameters in step (3c-3), it is possible to vary the surface appearance of the component according to the invention in terms of gloss from high gloss to non-glossy.

[0129] It is preferred that the component according to the invention is highly glossy, i.e. has a gloss value at a viewing angle of 60° of more than 90, preferably more than 95, particularly preferably more than 98. Gloss value in the context of the present application should be understood to mean the value determined in accordance with ISO 2813 (2015 edition).

[0130] When the support layer (I) is an injection-molded plastic support, an extruded sheet or an extruded profile, optionally thermoformed, this support layer (I) preferably has a thickness of 0.5 mm to 5 mm, particularly preferably 1.5 mm to 3.5 mm, particularly preferably 1.7 mm to 3.0 mm. This should be understood to mean that the support layer (I) has a thickness in these ranges at any point in the range, and it is preferred to use a support layer thickness of at most 3.0 mm, more preferably at most 2.5 mm, particularly preferably at most 2.2 mm in the transilluminated area. The layer does not necessarily have to have the same thickness over the entire area, but rather may have different thicknesses, for example, due to the configuration of the reinforcing ribs, the shape of the component, or the mounting structure, etc.

[0131] In a particular embodiment in which the support layer (I) in the multilayer article according to the invention is an extruded film, this film preferably has a thickness of 0.1 mm to 1 mm, more preferably 0.2 mm to 0.7 mm, particularly preferably 0.3 mm to 0.6 mm.

[0132] Such a film is suitable for film insert molding of the support layer (I) on the side opposite the visible side of the multilayer article using a thermoplastic molding compound with high light transmittance. The application of the metal layer on the side opposite the visible side of the multilayer article of the support layer (I) in the electroplating process as described above can be carried out either before or after film insert molding of the support layer film (I), preferably after film insert molding with a thermoplastic molding compound with high light transmittance.

[0133] In this case, in the following order: Preferably, the metal layer (II) is multi-ply. A support layer (I), and A film insert molding layer (III) composed of a thermoplastic molding compound having high light transmittance; A multi-layer article of at least three layers comprising:

[0134] The film insert molding layer (III), which is made of a thermoplastic molding compound having high light transmittance, preferably has a thickness of 0.5 mm to 5 mm, particularly preferably 1.5 mm to 3.5 mm, and particularly preferably 1.7 mm to 3.0 mm, and these values ​​should be understood as above.

[0135] The thermoplastic molding compound having high light transmittance suitable for forming the film insert molding layer (III) is preferably a molding compound made from a composition containing an aromatic polycarbonate. It is particularly preferred that the thermoplastic molding compound suitable for forming the film insert molding layer (III) is made from a composition containing at least one aromatic polycarbonate and at least one representative selected from the group consisting of release agents, stabilizers, flow promoters, dyes, pigments, and additives that increase the light scattering of polycarbonates. The content of the release agents, stabilizers, flow promoters, dyes, pigments, and additives that increase the light scattering of polycarbonates in these compositions is preferably 0.05% by weight to 10% by weight, particularly preferably 0.1% by weight to 5% by weight, and most preferably 0.2% by weight to 3% by weight in total.

[0136] In a preferred embodiment, the thermoplastic molding compound producing the film insert molding layer (III) has such a high light transmittance that the film insert molding layer (III) in its actual thickness has a transmittance of at least 40%, more preferably at least 50%, particularly preferably at least 60%, and most preferably at least 70%, at at least one wavelength in the wavelength range of the spectrum from 380 nm to 780 nm, where the transmittance is obtained from a transmission spectrum measured according to the standard in DIN / ISO 13468-2 (2006 edition).

[0137] Further embodiments of the present invention are described below:

[0138] 1. (I) a support layer composed of a thermoplastic molding compound containing the following A), B), and C); (II) a metal layer, preferably a multi-ply metal layer, containing at least one cutout; A multi-layer article comprising: A) at least one representative selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) a rubber-modified vinyl (co)polymer consisting of the following B.1) and B.2): C) optionally at least one further component selected from polymer additives and blending partner polymers, B.1) 80% to 95% by weight of structural units derived from at least one vinyl monomer, based on the rubber-modified vinyl (co)polymer B; and B.2) 5% to 20% by weight, based on the rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature below -50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene; Here, the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below; (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and not trapped in rubber particles; Including, (i.1) rubber particles grafted with a vinyl (co)polymer composed of structural units of B.1, and (i.2) vinyl (co)polymers also composed of structural units of B.1 entrapped in rubber particles as a separate dispersed phase, wherein the dispersed phase of (i) has a median diameter D50 of 0.7 μm to 2.0 μm as measured by ultracentrifugation; The thermoplastic molding compound contains less than 2% by weight of a rubber-based graft polymer different from component B), and The thermoplastic molding compound has a rubber content of at least 2.0% by weight; A multi-layer article, wherein the at least one cut-out is in the form of at least one symbol, a pattern, a hole, a line, or a letter, or in the form of dot-like cut-outs arranged in the form of at least one symbol, a pattern, a hole, a line, or a letter.

[0139] 2. The multilayer article of embodiment 1, wherein the thickness of the metal layer is from 5 μm to 200 μm.

[0140] 3. A multilayer article according to any of the previous embodiments, wherein the thickness of the metal layer is from 10 μm to 60 μm.

[0141] 4. A multilayer article according to any of the previous embodiments, wherein the thickness of the metal layer is from 30 μm to 50 μm.

[0142] 5. A multi-layer article according to any of the previous embodiments, wherein the metal layer is a multi-ply metal layer composed of at least three plies.

[0143] 6. The metal layers are made up of three metal plies, starting with the support layer (I): (i) a first ply of copper; (ii) a second ply of nickel; and (iii) a third ply of metal having high resistance to environmental influences; 3. The multi-layer article of any of the preceding embodiments, comprising:

[0144] 7. The metal layers are made up of four metal plies, starting with the support layer (I): (i) a first ply of nickel; (ii) a second ply of copper; (iii) a third ply of nickel; and (iv) a fourth ply of metal having high resistance to environmental influences; 3. The multi-layer article of any of the preceding embodiments, comprising:

[0145] 8. The multilayer article of any of the preceding embodiments 5 or 6, wherein the metal having high resistance to environmental effects is chromium.

[0146] 9. The multilayer article of embodiment 8, wherein the ply of chromium has a thickness of from 100 nm to 3 μm.

[0147] 10. The multilayer article of any one of embodiments 6-9 above, wherein the copper metal ply has a thickness of 10 μm to 50 μm.

[0148] 11. The multilayer article of any one of embodiments 6 to 10, wherein the nickel metal layer starting from the support layer (I) and continuing to the copper layer has a thickness no greater than half that of the copper metal layer below it.

[0149] 12. A multilayer article according to any of the preceding embodiments, wherein the support layer (I) is an injection molded body, an optionally thermoformed extruded sheet or an extruded profile, and the thickness of the support layer (I) is in the range of 0.5 mm to 5 mm.

[0150] 13. A multilayer article according to any of the preceding embodiments, wherein the support layer (I) has a thickness in the transilluminated area of ​​from 1.5 mm to 3.7 mm.

[0151] 14. The multilayer article according to any one of the preceding embodiments, wherein the support layer (I) is a film having a thickness of 0.1 mm to 1 mm.

[0152] 15. The multilayer article according to embodiment 14, wherein the support layer (I) is a film having a thickness of 0.3 mm to 0.6 mm.

[0153] 16. A multi-layer article comprising, in the following order: Preferably, the metal layer (II) is multi-ply. A support layer (I), and A film insert molding layer (III) composed of a thermoplastic molding compound produced from a composition containing an aromatic polycarbonate; 3. The multi-layer article of any of the preceding embodiments, comprising at least three layers comprising:

[0154] 17. The multilayer article according to embodiment 16, wherein the film insert molding layer (III) is formed from a thermoplastic molding compound made from a composition containing at least one aromatic polycarbonate and at least one representative selected from the group consisting of release agents, stabilizers, flow promoters, dyes, pigments, and additives that increase the light scattering of the polycarbonate.

[0155] 18. The multilayer article according to embodiment 17, wherein the content of the release agent, stabilizer, flow promoter, dye, pigment, and additive that increases the light scattering of the polycarbonate in the molding compound for producing the film insert molding layer (III) is 0.1% by weight to 5% by weight.

[0156] 19. A multilayer article according to any of the previous embodiments, wherein the support layer (I) is produced in an extrusion or blow molding process, the support layer (I) consisting of a thermoplastic molding compound containing a branched polycarbonate as component A.

[0157] 20. The multilayer article of any of the previous embodiments, wherein the support layer comprises 30% to 85% by weight of component A, 14% to 69% by weight of component B, and 0.05% to 20% by weight of component C.

[0158] 21. The multilayer article of any of the previous embodiments, wherein the support layer comprises 50% to 82% by weight of component A, 17% to 49% by weight of component B, and 0.1% to 10% by weight of component C.

[0159] 22. The multilayer article of any of the previous embodiments, wherein the support layer comprises 58% to 82% by weight of component A, 17% to 41% by weight of component B, and 0.2% to 5% by weight of component C.

[0160] 23. The multilayer article of any of the previous embodiments, wherein the support layer comprises 65% to 75% by weight of component A, 24% to 34% by weight of component B, and 0.3% to 2% by weight of component C.

[0161] 24. A multilayer article according to any of the previous embodiments, wherein the support layer comprises less than 1% by weight of a rubber-based graft polymer different from component B).

[0162] 25. A multilayer article according to any of the previous embodiments, wherein the support layer does not contain any rubber-based graft polymer different from component B).

[0163] 26. A multilayer article according to any of the previous embodiments, wherein the support layer has a rubber content in the range of 2.0% to 6% by weight.

[0164] 27. A multilayer article according to any of the previous embodiments, wherein the support layer has a rubber content in the range of 2.5% to 5% by weight.

[0165] 28. A multilayer article according to any of the previous embodiments, wherein the support layer has a rubber content in the range of 2.6% to 4.1% by weight.

[0166] 29. A multilayer article according to any of the previous embodiments, wherein the support layer has a rubber content in the range of 2.7% to 3.3% by weight.

[0167] 30. A multilayer article according to any of the previous embodiments, wherein component A of the support layer is an aromatic polycarbonate based on bisphenol A.

[0168] 31. A multilayer article according to any of the previous embodiments, wherein component B) of the support layer is produced by a bulk polymerization process.

[0169] 32. A multilayer article according to any of the previous embodiments, wherein component B) contains less than 100 ppm total of alkali metal and alkaline earth metal ions.

[0170] 33. A multilayer article according to any of the previous embodiments, wherein component B contains less than 20 ppm total of alkali metal and alkaline earth metal ions.

[0171] 34. A multilayer article according to any of the previous embodiments, wherein the support layer consists of components A, B, and C to the extent of at least 80% by weight.

[0172] 35. A multilayer article according to any of the previous embodiments, wherein the support layer consists of components A, B, and C to the extent of at least 95% by weight.

[0173] 36. The multilayer article of any of the previous embodiments, wherein the support layer consists of component A, component B, and component C.

[0174] 37. Use of a thermoplastic molding compound containing component A, component B and component C according to any of the above embodiments 1 and 20 to 36 as a support layer in a multilayer article, The multi-layer article comprises the following components: (I) support layer; (II) a metal layer, preferably a multi-ply metal layer, containing at least one cutout; Including, use.

[0175] 38. a) a multilayer article according to any one of embodiments 1 to 36; b) a light source emitting light having at least one wavelength within the wavelength range of the spectrum from 380 nm to 780 nm; A lighting unit or a display unit comprising: The light source b) is an illumination or display unit arranged such that the support layer (I) of the multilayer article a) is transilluminated by the light emitted by the light source b).

[0176] 39. An illumination or display unit as described in embodiment 38, wherein the light source is an LED light source.

[0177] 40. A method for producing a multi-layer article, comprising: (1) forming a plastic support from a thermoplastic molding compound comprising: A), B), and C) A) at least one representative selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) a rubber-modified vinyl (co)polymer consisting of the following B.1) and B.2): C) optionally at least one further component selected from polymer additives and blending partner polymers, B.1) 80% to 95% by weight of structural units derived from at least one vinyl monomer, based on the rubber-modified vinyl (co)polymer B; and B.2) 5% to 20% by weight, based on the rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature below -50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene; Here, the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below; (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and not trapped in rubber particles; Including, (i.1) rubber particles grafted with a vinyl (co)polymer composed of structural units of B.1, and (i.2) vinyl (co)polymers also composed of structural units of B.1 entrapped in rubber particles as a separate dispersed phase, wherein the dispersed phase of (i) has a median diameter D50 of 0.7 μm to 2.0 μm as measured by ultracentrifugation; The thermoplastic molding compound contains less than 2% by weight of a rubber-based graft polymer different from component B), and The thermoplastic molding compound has a rubber content of at least 2.0% by weight; (2) optionally covering at least a portion of the surface of the plastic support opposite the visible side of the multilayer article, and optionally a portion of the visible surface of the plastic support, with an electrostable layer, preferably a coating, which locally prevents chemical, electrochemical or physical metal deposition in process step (3a) and thereby locally prevents electroplating in this area of ​​the plastic support in process step (3c); (3) electrochemically depositing a metal layer, preferably multiple plies, onto the portions of the surface of the plastic support not covered with the electrostable layer in step (2); In addition, process step (3) includes the following sub-steps: (3a) producing a thin film metal layer, preferably a layer of palladium, copper or nickel, on a plastic support, preferably in a chemical, electrochemical or physical process selected from deposition from a colloidal solution, direct metallization or vapor deposition; (3b) optionally partially removing the thin metal layer produced in process step (3a) by a process preferably selected from etching or laser ablation to produce areas on the plastic support that are not covered with the thin metal film; (3c) electroplating a preferably multi-ply metal surface coating comprising at least one electrochemical metal deposition step; It should be noted that areas on the plastic support that are not covered with the thin metal film produced in process step (3b) are not electroplated; (4) optionally, by mechanical, chemical and / or physical processes, locally removing the preferably multi-ply metal layer applied to the surface of the plastic support, forming a breakthrough in said metal layer and locally exposing the surface of the plastic support; wherein at least one of optional process steps (2), (3b) and (4) is used in a process with the result that at least one cutout in the metal layer of the multiple plies occurs on the visible side of the multilayer article, and if in process step (3) a metal layer is also provided on the side opposite the visible side of the multilayer article, at least one cutout in the metal layer also occurs on the side opposite the visible side of the multilayer article. EXAMPLES

[0178] Ingredient A-1: Weight average molecular weight M of 24000 g / mol w (determined by GPC at room temperature in methylene chloride against BPA-PC standards)

[0179] Component A-2: Weight average molecular weight M of 28000 g / mol w (determined by GPC at room temperature in methylene chloride against BPA-PC standards)

[0180] Ingredient B-1: An acrylonitrile-butadiene-styrene (ABS) polymer produced in a bulk polymerization process, comprising a dispersed phase composed of rubber particles grafted with styrene-acrylonitrile copolymer based on polybutadiene rubber as a graft substrate, with the styrene-acrylonitrile copolymer entrapped as a separate dispersed phase, and a styrene-acrylonitrile copolymer matrix that is not chemically bonded to the rubber particles and is not entrapped in the rubber particles. Component B-1 has an A:B:S ratio of 23%:10%:67% by weight, and a gel content of 20% by weight, determined as the portion insoluble in acetone. The acetone-soluble portion of component B-1 has a weight average molecular weight M of 165 kg / mol. w(measured by GPC in tetrahydrofuran as solvent using polystyrene standards). The median particle size D50 of the dispersed phase is 0.85 μm, measured by ultracentrifugation. The melt volume flow rate (MVR) of component B-1, measured according to ISO 1133 (2012 edition) at 220° C. and a piston load of 10 kg, is 6.7 ml / 10 min.

[0181] Ingredient B-2: An acrylonitrile-butadiene-styrene-n-butyl acrylate (ABSBA) polymer produced in a bulk polymerization process, comprising a dispersed phase composed of rubber particles grafted with styrene-acrylonitrile-n-butyl acrylate terpolymer based on polybutadiene rubber as a graft substrate, with styrene-acrylonitrile-n-butyl acrylate terpolymer entrapped as a separate dispersed phase, and a styrene-acrylonitrile copolymer matrix that is not chemically bonded to the rubber particles and is not entrapped in the rubber particles. Component B-2 has an A:B:S:BA ratio of 22.5%:10%:63%:4.5% by weight, and a gel content of 19% by weight, determined as the portion insoluble in acetone. The acetone-soluble portion of component B-2 has a weight average molecular weight M of 115 kg / mol. w (measured by GPC in tetrahydrofuran as solvent using polystyrene standards). The median particle size D50 of the dispersed phase is 0.50 μm, measured by ultracentrifugation. The melt flow rate (MFR) of component C-1, measured according to ISO 1133 (2012 edition) at 220° C. and a piston load of 10 kg, is 28 g / 10 min.

[0182] Ingredient B-3 An acrylonitrile-butadiene-styrene graft polymer having a core-shell structure prepared by emulsion polymerization of a mixture of 27% by weight acrylonitrile and 73% by weight styrene, 43% by weight based on the ABS polymer, in the presence of 57% by weight based on the ABS polymer of particulate crosslinked polybutadiene rubber as a graft substrate, the polybutadiene rubber graft substrate having a bimodal particle size distribution with maxima at 0.28 μm and 0.40 μm, and a median particle size D50 of 0.35 μm as measured by ultracentrifugation.

[0183] Component B-3 does not contain styrene-acrylonitrile copolymer entrapped in rubber particles.

[0184] Ingredient B-4 Acrylonitrile-butadiene-styrene graft polymer with core-shell structure produced by emulsion polymerization of a mixture of 42% by weight of ABS polymer, 26% by weight of acrylonitrile and 74% by weight of styrene in the presence of agglomerated granular polybutadiene rubber as graft substrate, 58% by weight of ABS polymer.Compared to the graft substrate used in component B-3, this polybutadiene rubber graft substrate has a significantly broader monomodal particle size distribution.However, the median particle size D50 of 0.38 μm measured by ultracentrifugation is in the same range as that of component B-3.

[0185] Component B-4 does not contain styrene-acrylonitrile copolymer entrapped in rubber particles.

[0186] Ingredient B-5 It has an acrylonitrile content of 23% by weight and a weight average molecular weight M of 100,000 Da measured by GPC at room temperature in tetrahydrofuran using polystyrene standards. w A styrene-acrylonitrile copolymer produced in a bulk polymerization process having the formula:

[0187] Component C1: Pentaerythritol tetrastearate.

[0188] Component C-2: Irganox™ B900 (BASF, Ludwigshafen, Germany) A mixture of 80% by weight of tris(2,4-di-tert-butyl-phenyl)phosphite (Irgafos® 168) and 20% by weight of 2,6-di-tert-butyl-4-(octadecaneoxycarbonylethyl)phenol (Irganox® 1076).

[0189] Component C3: Irganox™ 1076 (BASF, Ludwigshafen, Germany) 2,6-Di-tert-butyl-4-(octadecaneoxycarbonylethyl)phenol.

[0190] Preparation and testing of the moulding compounds according to the invention The molding compounds were prepared in a ZSK25 twin-screw extruder from Coperion, Werner & Pfleiderer (Stuttgart, Germany) at a melt temperature of 260° C. and an applied vacuum of 100 mbar (absolute).

[0191] Test specimens were prepared in an Arburg 270 E injection molding machine at a melt temperature of 260°C and a mold temperature of 80°C.

[0192] The melt viscosity was measured according to ISO 11443 (2014 edition) at a temperature of 260°C and 1000s -1 The shear rate was determined.

[0193] The IZOD notched impact strength was determined in accordance with ISO 180 / 1A (2013 edition) on test bars with dimensions of 80 mm x 10 mm x 4 mm at temperatures ranging from -50 °C to 23 °C. Measurements at various temperatures were used to determine the ductile-brittle transition temperature as the temperature at which 50% of the specimens under test undergo brittle fracture and 50% undergo ductile fracture.

[0194] To determine the material ductility under multiaxial stress at low temperatures, puncture tests according to ISO 6603-2 (2002 edition) were carried out at -20°C on 10 specimens with dimensions of 60 mm x 60 mm x 2 mm in each case. The percentage of brittle fracture serves as a measure of the material ductility under multiaxial stress. Brittle fracture is to be understood as meaning a fracture failure in which a part of the specimen breaks during the puncture test and / or the specimen shows an unstable crack propagation, such that the specimen breaks completely in two along such a crack during the test.

[0195] The elastic modulus E and the elongation at break were determined in dumbbells with dimensions of 170 mm x 10 mm x 4 mm at a strain rate of 1 mm / min (elastic modulus) or 5 mm / min (elongation at break) at 23°C according to ISO 527 (1996 edition).

[0196] As a measure of the heat distortion resistance, the Vicat B / 120 softening temperature is determined in accordance with ISO 180 / 1A (2014 edition) on test bars having dimensions of 80 mm x 10 mm x 4 mm.

[0197] As a measure of the transilluminability, the total light transmittance was determined in accordance with ISO 13468-2 (2006 edition) (illuminant: D65, observer: 10°) on test specimens having dimensions of 60 mm x 40 mm x 2 mm (i.e. with a material thickness of 2 mm).

[0198] The half-power angle (HPA) of light intensity was used as a measure of light diffusivity. A larger half-power angle means stronger light scattering. The half-power angle is determined by measuring the intensity of light after transillumination of a test piece having dimensions of 60 mm × 40 mm × 2 mm (i.e., having a material thickness of 2 mm) according to the polar angle measured for the incident light beam in the range of 0° to 90°. The obtained values ​​are normalized to the intensity value measured at an angle of 0°, so that the normalized intensity varies between 0 and 1 according to the polar angle θ (where I(0°) = 1). The half-power angle (HPA) is defined as the angle at which the normalized intensity drops to 0.5 (i.e., I(HPA) = 0.5). According to this definition, the theoretical maximum possible half-power angle is 60°.

[0199] Composition 11 of the invention was used to manufacture shaped articles to which a metal layer could be applied in an electroplating process as described above.

[0200] [Table 1]

[0201] The data in table 1 make it clear that the inventive molding compounds, which contain as component B the inventive component B-1 and are within the scope of the invention in terms of the polybutadiene rubber content, show a surprisingly advantageous combination of improved light transmission and high light diffusion (scattering power). Moreover, the inventive molding compounds show an advantageous combination of improved melt flow (reduced melt viscosity) and good mechanical properties, in particular good material toughness even at low temperatures and high heat distortion resistance. In contrast, molding compounds not according to the invention, which contain as component B the inventive emulsion-polymerized ABS components B-3 or B-4 or the inventive bulk-polymerized ABS component B-2, are not able to achieve this technical problem of the invention. The same applies to the molding compounds composed of compositions V9 and V13, which are outside the scope of the invention in terms of the polybutadiene rubber content.

Claims

1. (I) a support layer composed of a thermoplastic molding compound containing the following A), B), and C); (II) a metal layer, preferably a multi-ply metal layer, containing at least one cutout; A multi-layer article comprising: A) at least one representative selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) A rubber-modified vinyl (co)polymer composed of the following B.1) and B.2); C) optionally at least one further component selected from polymer additives and blending partner polymers; B. 1) 80% to 95% by weight, based on said rubber-modified vinyl (co)polymer B, of structural units derived from at least one vinyl monomer; and B.2) 5% to 20% by weight, based on said rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature below -50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene; wherein the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below, (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and not trapped in rubber particles; Including, (i.1) B. Rubber particles grafted with a vinyl (co)polymer composed of structural units of 1, and (i.2) a vinyl (co)polymer composed of structural units of B.1 as well, entrapped in the rubber particles as a separate dispersed phase; wherein the dispersed phase of (i) has a median diameter D50 of 0.7 μm to 2.0 μm as measured by ultracentrifugation; wherein the thermoplastic molding compound contains less than 2% by weight of a rubber-based graft polymer different from component B), and The thermoplastic molding compound has a rubber content of at least 2.0% by weight; The at least one cutout is in the form of at least one symbol, a pattern, a hole, a line or a letter, or in the form of dot-like cutouts arranged in the form of at least one symbol, a pattern, a hole, a line or a letter.

2. The multilayer article of claim 1, wherein the metal layer has a thickness of from 5 μm to 200 μm.

3. 3. The multi-layer article of claim 1 or 2, wherein the metal layer is a multi-ply metal layer consisting of at least three plies.

4. The metal layers are made up of three metal plies, starting with the support layer (I): (i) a copper first ply; (ii) a second ply of nickel; and (iii) a third ply of chrome; The multilayer article according to any one of claims 1 to 3, which consists of

5. The metal layers are made up of four metal plies, starting from the support layer (I): (i) a first ply of nickel; (ii) a second ply of copper; (iii) a third ply of nickel; and (iv) a fourth ply of chrome; The multilayer article according to any one of claims 1 to 3, which consists of

6. The multilayer article of claim 4 or 5, wherein the ply of chromium has a thickness of from 100 nm to 3 μm.

7. A multilayer article according to any one of the preceding claims, wherein the thickness of the support layer (I) is in the range of from 0.5 mm to 5 mm.

8. The multilayer article according to any one of claims 1 to 6, wherein the support layer (I) is a film having a thickness of from 0.1 mm to 1 mm.

9. The multi-layer article is formed by: Preferably multi-ply metal layer (II), The support layer (I), and A film insert molding layer (III) composed of a thermoplastic molding compound made from a composition containing an aromatic polycarbonate; 9. The multilayer article according to claim 1, characterized in that it is composed of at least three layers comprising:

10. The support layer (I) is 30% to 85% by weight of component A, 14% to 69% by weight of component B, and 0.05% to 20% by weight of component C, The multilayer article of any one of claims 1 to 9, comprising:

11. A multi-layer article according to any one of claims 1 to 10, wherein the support layer has a rubber content of from 2.6% to 4.1% by weight.

12. The multilayer article according to any one of claims 1 to 11, wherein the support layer contains less than 1% by weight of a rubber-based graft polymer different from component B).

13. As a support layer in a multilayer article, A) at least one representative selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) A rubber-modified vinyl (co)polymer composed of the following B.1) and B.2); C) optionally at least one further component selected from polymer additives and blending partner polymers; Use of a thermoplastic molding compound comprising B. 1) 80% to 95% by weight, based on said rubber-modified vinyl (co)polymer B, of structural units derived from at least one vinyl monomer; and B.2) 5% to 20% by weight, based on said rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature below -50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene; wherein the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below, (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and not trapped in rubber particles; Including, (i.1) B. Rubber particles grafted with a vinyl (co)polymer composed of structural units of 1, and (i.2) a vinyl (co)polymer composed of structural units of B.1 as well, entrapped in the rubber particles as a separate dispersed phase; wherein the dispersed phase of (i) has a median diameter D50 of 0.7 μm to 2.0 μm as measured by ultracentrifugation; wherein the thermoplastic molding compound contains less than 2% by weight of a rubber-based graft polymer different from component B), and The thermoplastic molding compound has a rubber content of at least 2.0% by weight; The multi-layer article comprises the following components: (I) the support layer, (II) a metal layer, preferably a multi-ply metal layer, containing one or more cutouts; Including, use.

14. a) the multilayer article of any one of claims 1 to 12, b) a light source emitting light having at least one wavelength within the wavelength range of the spectrum from 380 nm to 780 nm; A lighting unit or a display unit comprising: The light source b) is arranged in such a way that the support layer (I) of the multilayer article a) is transilluminated by the light emitted by the light source b), in an illumination unit or display unit.

15. 1. A method for making a multi-layer article, comprising: (1) forming a plastic support from a thermoplastic molding compound comprising the following: A), B), and C); A) at least one representative selected from the group consisting of aromatic polycarbonates and aromatic polyester carbonates; B) A rubber-modified vinyl (co)polymer composed of the following B.1) and B.2); C) optionally at least one further component selected from polymer additives and blending partner polymers; B. 1) 80% to 95% by weight, based on said rubber-modified vinyl (co)polymer B, of structural units derived from at least one vinyl monomer; and B.2) 5% to 20% by weight, based on said rubber-modified vinyl (co)polymer B, of one or more elastomeric graft substrates having a glass transition temperature below -50°C and containing at least 50% by weight, based on B.2, of structural units derived from 1,3-butadiene; wherein the rubber-modified vinyl (co)polymer B is (i) a dispersed phase consisting of (i.1) and (i.2) below, (ii) a rubber-free vinyl (co)polymer matrix consisting of structural units of B.1 that are not bonded to and not trapped in the rubber particles; Including, (i.1) B. Rubber particles grafted with a vinyl (co)polymer composed of structural units of 1, and (i.2) a vinyl (co)polymer composed of structural units of B.1 as well, entrapped in the rubber particles as a separate dispersed phase; wherein the dispersed phase of (i) has a median diameter D50 of 0.7 μm to 2.0 μm as measured by ultracentrifugation; wherein the thermoplastic molding compound contains less than 2% by weight of a rubber-based graft polymer different from component B), and The thermoplastic molding compound has a rubber content of at least 2.0 weight percent; (2) optionally covering at least a part of the surface of the plastic support opposite the visible side of the multilayer article, and optionally a part of the visible surface of the plastic support, with an electrostable layer, preferably a coating, which locally prevents chemical, electrochemical or physical metal deposition in process step (3a) and thereby locally prevents electroplating in this area of ​​the plastic support in process step (3c); (3) electrochemically depositing a metal layer, preferably multiple plies, onto the portions of the surface of the plastic support not covered with an electrostable layer in step (2); It should be noted that process step (3) includes the following sub-steps: (3a) producing a thin film metal layer, preferably a layer of palladium, copper or nickel, on said plastic support, preferably in a chemical, electrochemical or physical process selected from deposition from a colloidal solution, direct metallization or vapor deposition; (3b) optionally partially removing the thin metal layer produced in process step (3a) by a process preferably selected from etching or laser ablation to produce areas on the plastic support that are not covered by the thin metal film; (3c) electroplating a preferably multi-ply metal surface coating comprising at least one electrochemical metal deposition step; However, areas on the plastic support that are not covered with the thin metal film produced in process step (3b) are not electroplated; (4) optionally locally removing, by mechanical, chemical and / or physical processes, the preferably multi-ply metal layer applied to the surface of the plastic support, forming breakthroughs in the metal layer and locally exposing the surface of the plastic support; and using at least one of optional process steps (2), (3b) and (4) preferably in a process with the result that at least one cutout in the multi-ply metal layer occurs on the visible side of the multilayer article, and if in process step (3) a metal layer is also provided on the opposite side to the visible side of the multilayer article, at least one cutout in the metal layer also occurs on the opposite side to the visible side of the multilayer article.

Citation Information

Patent Citations

  • Galvanizing plastic components with haptic and optical interrupt structures, comprises applying island structures on non-galvanizable plastic component, and applying island surface from galvanically stable medium on injection-moldable film

    DE102010053165A1

  • Galvanically coated element production, comprises forming a base body, covering or screening region on the rear side, chemically and optionally galvanically pre-treating the base body, and galvanically forming a metallic surface coating

    DE10208674A1

  • Process for the production of translucent, electroplated thermoplastic parts and translucent thermoplastic parts with an electroplated surface

    DE10320237A1

  • Electroplated component with a symbolism or structure incorporated into the surface that allows it to be seen through.

    DE202013009793U1

  • Metallized plastic component having a transilluminable structure in day and night design; method for producing the plastic component

    WO2017063768A1